Constricted spatiotemporal foraging of the regenerating salamander, Bolitoglossa mombachoensis - Roger A. Mendieta Donaire; Jose M. Zolotoff Pallais; Ji Suk Chung; Maria A. Cobos Rizo; Marcelo De los Santos Rosales; Jiehong Jun Lee; Roberto M. Sandino Jaen; Elinor M. Ketelhohn Clancy; Martin M. Casco‐Robles (Ecosphere, 2019)
Abstract Bolitoglossa mombachoensis is an endemic neotropical salamander of the Mombacho Volcano, Nicaragua. Canopy communities within the tropics are hubs for biodiversity, and many tropical plethodontids have a foraging preference for epiphytic plants, such as bromeliads, which provide moist microclimates for shelter, foraging, and nesting. Habitat loss continues to be the biggest threat to amphibians worldwide. This species is highly dependent on nocturnal arboreal climbing. We describe their plant preference, which extends beyond bromeliads, and their arboreal dependence used for refuge and foraging. Foraging behavior is constricted to nighttime, plant availability, geography, and altitude.